Repeated biodisinfection controls the incidence of Phytophthora root and crown rot of pepper while improving soil quality - Nuñez-Zofío, M.; Larregla del Palacio, S.; Garbisu, C. (Spanish Journal of Agricultural Research, 2012)
Phytophthora root and crown rot is a plant disease responsible for important economic losses in protected pepper crops. A greenhouse experiment was carried out in a temperate climate region (northern Spain) to assess the effects of repeated biodisinfection after three consecutive crop seasons with different organic amendments (a non-composted mixture of sheep manure and chicken litter, a semicomposted mixture of horse manure and chicken litter, Brassica carinata dehydrated pellets plus Sinapis alba fresh green manure) on disease incidence, crop yield and soil quality. Biodisinfection treatments were found to improve soil water properties through reduction in soil bulk density and increased water infiltration. Biodisinfested soils showed higher values of physicochemical and microbial properties than control (untreated) and plastic-mulched soils. In plots treated with the non-composted or semicomposted mixture, the observed higher levels of microbial activity were strongly related with an increase in soil microbial biomass. Brassica-Sinapis treatment had a weaker effect on soil properties than animal manure-based treatments. However, highest counts of total bacteria, actinomycetes and Pseudomonas spp. were found in Brassica-Sinapis-treated soils. It was concluded that repeated biodisinfection for the control of Phytophthora root and crown rot in protected pepper crops located in temperate climate regions can improve soil quality and suppressiveness, as well as allow for a reduction in the dose of organic amendment needed for biodisinfection. Among the studied organic amendments, the semicomposted amendment was the best option in terms of reduction in disease incidence.